(untitled) (Tempo e Argumento, 2021)
The objective of this article is to discuss the impacts of the Internet age on the profession of historian with emphasis on historical research and forms of mediation, as well as diffusion of historical knowledge in the public extent of digital media. Based on bibliographic analysis of sources, it discusses the epistemological and methodological challenges that the so-called digital revolution imposed on professionals in the field of History. It endorses the importance of digital history for the understanding of contemporary human experiences and suggests a definition for this field based on the digital character of its objects of study. It also points out the need for readjustments in the method of historical criticism supporting that new interdisciplinary dialogues are essential for the diversification of the methodological repertoire of historical research in view of the challenges that arise from the analysis of digital sources. Afterwards, it addresses the transformations caused by digital culture in relation to forms of mediation and diffusion of historical knowledge to a wide audience, demonstrating that the current resources of the web have brought new possibilities and challenges to practitioners of a digital public history. Finally, it discusses the social function of the historian at a time marked by the complex phenomena of fake news and post-truth, highlighting the importance of the role of historians in the public extent of digital media to fight against attempts to fake reality and historical denial. Keywords: digital history; digital public history; Internet; fake news; post-truth.